Experimental study on permanent image sticking of single and double barrier ribs in alternating-current plasma display panel. (4th March 2017) - Park, Choon-Sang; Jung, Eun Young; Kim, Dong Ha; Kim, Hyun-Jin; Seo, Heaseok; Kim, Sung-O; Shin, Bhum Jae; Tae, Heung-Sik
ABSTRACT: The permanent image sticking phenomena were examined and compared for the two different barrier rib structures such as the single and double barrier ribs. To compare the permanent image sticking phenomena for both barrier rib structures, the differences in the display luminance, address discharge delay time, firing voltage, visible light profile, impulse, and SEM image of the image sticking cells during long time discharges were measured. The proposed double barrier structure showed that the variations in the surface states of the MgO layer remained almost the same between ITO and bus electrodes during long time discharges, thereby reducing the difference of the luminance and statistical address delay times. As a result, the double barrier rib structure was observed to mitigate the permanent image sticking in comparison with the single barrier rib structure in the 50 in full HD ac-PDPs with a He (35%)-Xe (11%)-Ne contents.